Guanxinning for Residual Inflammation of Stable Coronary Artery Disease: A Pilot Randomized Controlled Trial - Chen T; Zheng J; Bao C; Wang Y; Wang S; Liang L; Zhang L; Zhang H; Ji C; Wang J; Zhang X; Zhu G; et al. (Dove Medical Press, 2024)
Tielong Chen,1,* Jianwu Zheng,1,* Cheng Bao,1 Yu Wang,1 Shiwang Wang,1 Lu Liang,1 Li Zhang,2 Hui Zhang,2 Chaoxia Ji,2 Jian Wang,2 Xudong Zhang,1 Guangli Zhu,1 Houyong Zhu1 1Department of Cardiology, Hangzhou TCM Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China; 2Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Tielong Chen; Houyong Zhu, Department of Cardiology, Hangzhou TCM Hospital Affiliated to Zhejiang Chinese Medical University, No. 453 Stadium Road, Hangzhou, Zhejiang, 310007, People's Republic of China, Email ctlppp@foxmail.com, ctlppp@163.com; houyongzhu@foxmail.comBackground: Despite statins and other medications central to atherosclerotic cardiovascular disease (ASCVD) secondary prevention, stable coronary artery disease (SCAD) patients remain at significant cardiovascular risk, partly due to residual inflammation risk (RIR). This study aims to assess if adding Guanxinning to standard ASCVD therapy further mitigates RIR in SCAD patients.Methods: In a prospective, randomized, single-blind endpoint design, 50 patients with SCAD who received ASCVD standardized treatment strategy were randomly assigned to either take Guanxinning tablets (4 tablets, thrice daily) or no Guanxinning tablets and were followed up for an average of 12 weeks. The primary outcomes were changes in inflammation-related indicators, including interleukin-2 (IL-2), IL-4, IL-6, tumor necrosis factor-α (TNF-α), and high sensitivity C-reactive protein (hs-CRP).Results: Compared with the control group, the intervention group showed significantly greater decreases in the levels of IL-2, IL-6, TNF-α, and hs-CRP (all P < 0.05). However, there was no significant difference in the IL-4 level between the two groups (P > 0.05). Compared with the control group, there were also significant improvements in endothelial function-related indicators (vascular endothelial growth factor (VEGF), nitric oxide (NO), and peroxisome proliferator-activated receptor-γ (PPAR-γ)), blood lipid profile (total cholesterol (Tch), low-density lipoprotein cholesterol (LDL-C)), and chest pain related scores (angina and Traditional Chinese medicine syndrome scores) in the intervention group (all P< 0.05). There was no significant difference in the triglyceride (TG) and carotid intima-media thickness between the two groups (P< 0.05). Compared to the control group, there was no significant difference in the white blood cell line, liver and kidney function, anemia, and bleeding in the intervention group (all P< 0.05).Conclusion: The addition of Guanxinning tablets (4 tablets, thrice daily) to the standard treatment strategy for ASCVD was associated with a reduction in the RIR in patients with SCAD and demonstrated good safety.Plain Language Summary: In the quest for a heart-healthy life, even with statins at our side, some folks with stable heart troubles still face a sneaky foe: lingering inflammation. Our study explored whether adding Guanxinning, a traditional Chinese medicine, to the standard treatment might help. Over 12 weeks, patients who took Guanxinning along with their usual heart meds showed promising signs of reduced inflammation and improved heart health markers. These preliminary positive signs hint at the potential benefits of Guanxinning, which, however, need further studies to confirm. Fortunately, it appears to be safe to use Guanxinning alongside conventional treatments for now. As we delve deeper into the mysteries of heart health, every promising discovery brings us one step closer to developing better therapeutic strategies.Keywords: Guanxinning, stable coronary artery disease, risk of residual inflammation, secondary prevention